Development of a WhatsApp Chatbot as a Nutrition Education Media for Mothers of Toddlers - Umu Sholihah; Sarwanto; Fatma Sukmawati (Institut Attanwir Bojonegoro, 2024)
The Quran commands Muslims to contemplate the signs of Allah in the creation of the heavens and the earth. This includes an understanding of nutrition and dietary practices, enabling mothers to provide healthy and nutritious food for toddlers. The dissemination of reliable information, especially health-related information, has become a significant concern during the Covid-19 pandemic. The objective of this research is to create a WhatsApp chatbot that can serve as a useful and efficient tool for providing essential nutrition information to mothers of toddlers. The research method employed by the researcher is the Prototype Model research method. Prototyping is an approach in software development that involves creating a physical model of a system that can function and represent an initial version of the system under development. The prototyping method is used to generate a system prototype that acts as a bridge between developers and users, allowing them to interact during the information system development process. The research results indicate that the access to nutrition information still relies on conventional methods like lectures and guidebooks for dissemination, which have not significantly impacted the prevention of stunting. Therefore, the development of a WhatsApp chatbot is highly necessary. The researcher has utilized the Human-Computer Interaction (HCI) theory and materials with the characteristics of the 1000 HPK theory as a foundation for developing the WhatsApp chatbot. This research will serve as a valuable tool for accessing nutrition information that can be accessed anytime and anywhere.